Gruppenaufnahme - Nicole Maskus
Vorsitzender CDU-Landesverband Nordrhein-Westfalen Jürgen Rüttgers; CDU-Generalsekretärin Angela Merkel; Ministerpräsident Thüringen Bernhard Vogel; CDU-Vorsitzender Wolfgang Schäuble;